Level of Mental Health among Syrian Refugees in Jordan - Momani, Fawwaz Ayoub (Dirasat: Educational Sciences, 2020)
The current study aims to reveal the level of mental health among Syrian refugees in Jordan. To achieve the study objectives, the researchers used the mental health scale after its arabization (Mental Health Inventory-18 (MHI-18). The study sample consisted of (1095) male and female refugees were chosen based on the convenient sample, and a descriptive methodology was followed. The results showed the level of mental health among subscales were moderate. The study results indicated that there were statistically significant differences on mental health on some subscales attributed to variables (gender, number of years of residence in Jordan, place of residence, age, and marital status), and there were no statistically significant differences attributed to educational level. The study recommends enhancing the level of support and psychological services presented to Syrian refugees in hosting communities to insure achieving the highest possible level of mental health and wellbeing; with a priority in targeting female refugees.